Molecular based detection, validation of a LAMP assay and phylogenetic analysis of Capripoxvirus in Kenya - Omoga, D.C.A.; Macharia, M.; Magiri, E.; Kinyua, J.; Kasiiti, J.; Holton, T. (Sciencedomain International, 2016)
Aims: To optimize the different available molecular based techniques, validate the Loop-mediated isothermal amplification (LAMP) assay for detection of Capripoxviruses (CaPVs) DNA and deep sequencing to confirm the results of the LAMP assay and ensure that an effective and reliable detection method is recommended and adopted for use in Capripox diagnosis. The phylogenetic analysis was also to determine CaPVs genome variability, evolution, and diversity. Study Design: It included sample collection, DNA extraction, analysis and sequencing. Place and Duration of Study: Biosciences East and Central Africa-International Livestock Research Institute (BecA-ILRI) Hub, between May 2014 and March 2015. Methodology: We analyzed 130 samples including blood, skin nodules and cell cultures from symptomatic and suspected sheep, goats and cattle. The samples were tested by, conventional PCR, LAMP assay and real time PCR as the gold standard method, the results obtained were compared and used to determine sensitivity and specificity. The Limit of detection (LOD) of real time PCR and LAMP assay was determined using a serially diluted positive sample. Deep sequencing of 18 LAMP positive samples from different parts of the country was done and the obtained sequenced data analyzed using bioinformatics platform. Results: The disease prevalence in the population was 61%, The validated LAMP assay had a 97% sensitivity and a specificity of 100%. Using the Fisher's Exact Tests, a P-value of (P = .8) at 95% interval was obtained. This shows that there is no significant difference between the validated LAMP Assay and the gold standard method. The Phylogenetic analysis of the 3 important CaPVs genes revealed the distribution of CaPVs into the 3 major specific lineages. Conclusion: This study supports the adoption of LAMP assays for CaPVs diagnosis as a rapid and robust method of detection, disease monitoring and controlling outbreaks. The sequence data confirms the possibility of cross infection, nonhost specificity of CaPVs and also provides a reference in genomic research and a basis for molecular epidemiological studies in Kenya.